Kegiatan Penapisan Antropometri pada Usia Produktif sebagai Parameter Obesitas di SMAN 75, Jakarta - Jeffrey Jeffrey; Gunaidi, Farell Christian; Kurniawan, Junius; Amanda, Shelma Tria (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
Obesity in children and adolescents is a global health problem, with increasing prevalence in low- and middle-income countries and consistently high obesity rates in high-income countries. Obesity, characterized by excessive lipid accumulation, is primarily caused by an energy imbalance resulting from high caloric intake and inadequate expenditure. This activity uses the PDCA (Plan-Do-Check-Act) methodology, involving 167 participants for obesity screening. The results of measuring Body Mass Index and waist circumference showed that 14 (8.39%) people were obese level II, 22 (13.18%) people were obese level I, 13 (7.79%) people were overweight, and 53 ( 31.74%) people have a risk of central obesity. Early detection through routine anthropometric assessments allows timely intervention, including lifestyle modifications to prevent obesity and related comorbidities, thereby improving overall health outcomes.